130k views
5 votes
Write the equation for the inverse of the function y=Cos^-1(x-pi)

Write the equation for the inverse of the function y=Cos^-1(x-pi)-example-1

2 Answers

7 votes

Answer:

The answer is C

Explanation:

User Kodaloid
by
5.8k points
3 votes

we are given


y=cos^(-1)(x-\pi)

Since, we have to find inverse function

step-1:

Set y=f(x)

It is already there

step-2:

Switch x and y


x=cos^(-1)(y-\pi)

step-3: Solve for y

We can take cos on both sides


cos(x)=cos(cos^(-1)(y-\pi))

we can simplify it


cos(x)=y-\pi

now, we can solve for y


cos(x)+\pi=y-\pi+\pi


cos(x)+\pi=y


y=\pi +cos(x)..............Answer


User Gjulianm
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.